The effects of hormones, growth factors and cyclic AMP on ovarian carcinoma cell proliferation and expression of c-kit and Kit ligand. - Keszthelyi, Eniko Judith. (University of Ottawa (Canada), 1998)
The protooncongene c-kit encodes a tyrosine kinase receptor (Kit) that is activated by its ligand KL to promote proliferation, survival and migration of Kit-bearing cells. In addition to its ability to induce transformation in transfected cells, c-kit is overexpressed in many cancers, including those of the ovary. The goal of this research project was to examine the regulation of c-kit and KL expression in ovarian carcinoma cells, by factors which are produced by, and/or act on the ovary, such as steroid and gonadotropic hormones, and growth factors. Studies were completed using two ovarian carcinoma cell lines, HEY and OVCA 429, which are both c-kit- and KL-bearing, as in vitro model systems for ovarian carcinoma. Using these 2 cell lines, the effects on proliferation and c-kit and KL mRNA expression of: epidermal growth factor (EGF), transforming growth factors-$\alpha$ and $\beta$ (TGF-$\alpha$ and TGF-$\beta$), estradiol (E$\sb2),$ progesterone (P$\sb4),$ testosterone (T), follicle stimulating hormone (FSH), human chorionic gonadotropin (hCG), cyclic adenosine monophosphate (cAMP) analogues (dibutyryl-adenosine-3$\sp\prime$:5$\sp\prime$-monophosphate, cyclic (dbcAMP) and 8-bromo-adenosine-3$\sp\prime$:5$\sp\prime$-monophosphate, cyclic (8-bromo-cAMP)) and an adenylate cyclase activator (cholera toxin) were determined. (Abstract shortened by UMI.)
Keywords: Biology, Cell.